Framework untuk Pengembangan Sistem Otomatisasi Menggunakan Programmable Logic Controller - Rochim, Adian Fatchur; Widianto, Eko Didik (Jurnal Sistem Komputer, 2011)
Nowadays, the programmable logiccontroller/PLC has been a key device in industrial automation. This device has a function to monitor production process and to control its operation automatically. This paper presents a framework to develop this product service-system PLC using opensource softwares. It includes software for PLC hardware development, firmware development and IDE system.